EFFECT OF THE LOG STORAGE OF Pinus taeda L. ON THE QUALITY OF KRAFT PULP - Giesel, Guilherme; Brand, Martha Andreia; Milagres, Flaviana Reis; Damasio, Renato Augusto Pereira (Floresta, 2020)
In pulp production, wood in logs is stored for periods that can range from a few weeks to several months. During storage, changes in the wood properties that affect the pulping process and the quality of the pulp may occur. The objective of this study was to determine the ideal timing of wood storage in logs by evaluating the variations (a) in the chemical properties of wood (b) in the parameters of the pulping process and (c) the quality of the Pinus taeda pulp. Logs were stored in an industrial courtyard for 30, 60, 90, 120 and 150 days. In each storage period, the physical and chemical properties of the wood, the cooking parameters, and the properties of the pulp were analyzed. The chemical properties of wood varied throughout storage, but only the solubility in sodium hydroxide showed a positive and significant correlation with storage time. In pulping, the yield and tailings had an inversely proportional correlation with the storage time, while the organic and total solids content had a positive correlation. As for cellulose quality, arabinan and soluble lignin contents did not vary during storage. The mannan content had a positive and significant correlation with the storage time. Taking into account all the variables analyzed, the storage time of P. taeda logs should be up to 30 days.